2016
DOI: 10.1093/carcin/bgw011
|View full text |Cite
|
Sign up to set email alerts
|

The feedback loop between miR-124 and TGF-β pathway plays a significant role in non-small cell lung cancer metastasis

Abstract: Increasing evidence shows that micro RNAs (miRNAs) play a critical role in tumor development. However, the role of miRNAs in non-small cell lung cancer (NSCLC) metastasis remains largely unknown. Here, we found that miR-124 expression was significantly impaired in NSCLC tissues and associated with its metastasis. In vitro and in vivo experiments indicate that restoring miR-124 expression in NSCLC cells had a marked effect on reducing cell migration, invasion and metastasis. Mechanistic analyses show that Smad4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 43 publications
4
43
1
Order By: Relevance
“…miRNAs can function as oncogenes or tumor suppressor genes in cancer, aiming at restoration of tumor suppressor genes and silence of oncogenes would be a novel anticancer therapy (23). The inhibitory effect of miR-124 in tumor growth and migration, as well as dysregulation of miR-124 has been reported in various tumor types (6)(7)(8)(9). In a previous (13) and the present study, miR-124 was downregulated in GC tissues and cell lines.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…miRNAs can function as oncogenes or tumor suppressor genes in cancer, aiming at restoration of tumor suppressor genes and silence of oncogenes would be a novel anticancer therapy (23). The inhibitory effect of miR-124 in tumor growth and migration, as well as dysregulation of miR-124 has been reported in various tumor types (6)(7)(8)(9). In a previous (13) and the present study, miR-124 was downregulated in GC tissues and cell lines.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, miR-124 has been found down-regulated in multiple tumor types, including cancer (6), prostate (7), lung (8) and colorectal cancer (9). It also been found that miR-124 could inhibit the proliferation of GC cells proliferation by targeting Rho-associated protein kinase 1, enhancer of zeste homolog 2 (EZH2) and sphingosine kinase 1 (SPHK1) (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…A strong relationship between miRNA and pathophysiological processes has been reported in the literature [20,21]. As mentioned in the literature review, miR-124 is frequently expressed in multiple tissues to regulate different pathophysiologic processes, for instance, the development of cancer [22][23][24][25][26], as a new therapeutic approach to Parkinson's disease [27], promotes the pathogenesis of Crohn's Disease [28] and contributes to cholangiocyte proliferation in the cholestatic liver [29].…”
Section: Discussionmentioning
confidence: 97%
“…In lung cancer, high TGF-β serum levels is associated with a poor prognosis, lymph node metastasis, and tumor progression (40,41). In addition, TGF-β was suggested as an independent risk factor for the occurrence of pulmonary metastasis in NSCLC (42). A study also revealed that the presence of p-SMAD2 and 3 was significantly higher in the NSCLC cancer tissues compared with the tumor-free lung tissues (3).…”
Section: Discussionmentioning
confidence: 99%